2017
DOI: 10.3389/fncel.2017.00122
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Elp3 Impairs the Acetylation and Distribution of Connexin-43 in the Developing Cerebral Cortex

Abstract: The Elongator complex is required for proper development of the cerebral cortex. Interfering with its activity in vivo delays the migration of postmitotic projection neurons, at least through a defective α-tubulin acetylation. However, this complex is already expressed by cortical progenitors where it may regulate the early steps of migration by targeting additional proteins. Here we report that connexin-43 (Cx43), which is strongly expressed by cortical progenitors and whose depletion impairs projection neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 66 publications
(115 reference statements)
1
18
0
Order By: Relevance
“…In detail, Elongator-dependent modifications of uridines in the wobble position of tRNA anticodons seem to be of key importance for the fidelity and kinetics of translational elongation, which also guides and directs cotranslational folding dynamics 8 , 9 . Over the past decade, a number of studies have showed that the Elongator complex is involved in various cellular activities that govern the development and maintenance of the nervous system 10 14 . Moreover, several studies have linked the occurrence of specific mutations in Elongator subunits with the onset of various neurological disorders 15 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In detail, Elongator-dependent modifications of uridines in the wobble position of tRNA anticodons seem to be of key importance for the fidelity and kinetics of translational elongation, which also guides and directs cotranslational folding dynamics 8 , 9 . Over the past decade, a number of studies have showed that the Elongator complex is involved in various cellular activities that govern the development and maintenance of the nervous system 10 14 . Moreover, several studies have linked the occurrence of specific mutations in Elongator subunits with the onset of various neurological disorders 15 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In this report, it is indicated that Cx43 favors cell-to-cell contact by interacting with elongator complex elements such as Elp1 and Elp3, allowing the acetylation of Cx43 and its membrane localization (Laguesse, 2017). Such membrane destination of Cx43 dependent on acetylation levels has also been reported in HeLa cells (Laguesse, 2017). An important observation in these studies is that channel activity was not required for neuronal migration.…”
Section: Regulation Of Cell Migration By Connexinsmentioning
confidence: 78%
“…On the other hand, Cx43 favors migration of projection neurons over radial glial cells in the developing brain (Laguesse, 2017). In this report, it is indicated that Cx43 favors cell-to-cell contact by interacting with elongator complex elements such as Elp1 and Elp3, allowing the acetylation of Cx43 and its membrane localization (Laguesse, 2017).…”
Section: Regulation Of Cell Migration By Connexinsmentioning
confidence: 87%
See 1 more Smart Citation
“…We will need to understand if different Elongator subunits and regulatory factors are targets of specific signaling cascades and show cell type specific functions in multicellular organisms (e.g., different neuronal subtypes within the central nervous system). Indeed, recent studies have highlighted the specific involvement of Elongator in the differentiation and migration of only a subset of projection neurons .…”
Section: Discussionmentioning
confidence: 99%